2015
DOI: 10.1080/20445911.2015.1074242
|View full text |Cite
|
Sign up to set email alerts
|

Voluntary language switching in English–Spanish bilingual children

Abstract: Although bilingual children frequently switch between languages, the psycholinguistic mechanisms underlying the emerging ability to control language choice are unknown. We examined the mechanisms of voluntary language switching in English-Spanish bilingual children during a picture-naming task under two conditions: 1) single-language naming in English and in Spanish; 2) either-language naming, when the children could use whichever language they wanted. The mechanism of inhibitory control was examined by analyz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(76 citation statements)
references
References 63 publications
6
70
0
Order By: Relevance
“…This asymmetry arises due to the greater amount of inhibition required to suppress a more dominant L1 while speaking in L2 [33]. Several studies have failed to observe this asymmetry [34],[35],[36],[37],[38], particularly during voluntary naming [8]. Since our participants were highly proficient in both their languages, it is possible that asymmetrical costs were not incurred during switching.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This asymmetry arises due to the greater amount of inhibition required to suppress a more dominant L1 while speaking in L2 [33]. Several studies have failed to observe this asymmetry [34],[35],[36],[37],[38], particularly during voluntary naming [8]. Since our participants were highly proficient in both their languages, it is possible that asymmetrical costs were not incurred during switching.…”
Section: Discussionmentioning
confidence: 99%
“…All two-way and three-way interactions were included except in cases where the model could not converge. In accordance with previous analysis on large psycholinguistic data [7],[8], the statistical significance of effects was determined using t values. Absolute t values greater than or equal to 1.96 were considered statistically significant; absolute t values greater than or equal to 1.65 but less than 1.96 were taken to be marginally significant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…As age (Best, Miller, & Jones, 2009), SES (Morton & Harper, 2007) and non-verbal IQ (Arffa, 2007; but see Ardila, Pineda, & Rosselli, 2000) have been shown to be related to cognitive functioning, we included these as control variables. Vocabulary and morphology scores in both languages were also taken into account as control variables, as previous research has shown that language proficiency may be related to both cognitive control (Bohlmann, Maier, & Palacios, 2015) and code-switching behaviour (Gross & Kaushanskaya, 2015;Yow et al, 2017). As expected, the children were quite proficient in both Dutch and Frisian, as revealed by their scores on Dutch and Frisian vocabulary (Peabody Picture Vocabulary Test-III-NL (PPVT-III-NL), Schlichting, 2005; Frisian adaptation, Bosma, Blom, Hoekstra, & Versloot, 2016) and Dutch and Frisian morphology (Taaltoets Alle Kinderen; Verhoeven & Vermeer, 2002;Frisian adaptation, Blom & Bosma, 2016), presented in Table 2.…”
Section: Participantsmentioning
confidence: 99%